Current status of surgery first approach (part II): precautions and complications - Tae-Geon Kwon; Michael D. Han (SpringerOpen, 2019)
Abstract The choice of surgical technique in orthognathic surgery is based primarily on the surgical treatment objectives (STO), which is a fundamental component of the orthognathic treatment process. In the conventional orthodontics-first approach, presurgical planning can be performed twice, during the preorthodontic (initial STO) and presurgical phases (final STO). Recently, a surgery-first orthognathic approach (SFA) without presurgical orthodontic treatment has been introduced and combined initial and final STO at the same time. In contrast to the conventional surgical-orthodontic treatment protocol that includes preoperative orthodontics for dental decompensations to maximize stable postoperative occlusion, the SFA potentially shortens the treatment period and minimizes esthetic concerns during the decompensation period because skeletal problems are corrected from the beginning. The indications for the SFA have been proposed in the literature, but no consensus exists. Moreover, because dental occlusion of the pre-orthodontic arches cannot be used as a guide for establishing the surgical treatment plan, there are fundamental limitations in accurate prediction of postsurgical results in the SFA. Recently, the concepts of postsurgical orthodontic treatment are continuously changing and evolving to overcome this inherent limitation of the SFA. The elimination of presurgical orthodontics can change the paradigm of orthognathic surgery but still requires cautious case selection and thorough discussion and collaboration between orthodontists and surgeons regarding the goals and postoperative management of the orthognathic procedure.